Predictive biomarkers of response to immune checkpoint inhibitors - María Sacramento Díaz-Carrasco; Eva González-Haba; Juana Inés García-Soler; Alberto Espuny-Miró (Farmacia Hospitalaria)
Objective: The present paper provides a literature review aimed at identifying the tumor-dependent factors capable of influencing a subject’s response to immune checkpoint inhibitors, with a special emphasis on those that may act as predictive biomarkers. Method: A search was performed of the terms biomarkers, PD-1, PD- L1, CTLA-4, and checkpoint inhibitors in the title and the abstract of the records in the PubMed database. Articles including relevant information on the tumor-dependent factors capable of influencing a subject’s response of immune checkpoint inhibitors were selected. Priority was given to studies in humans (clinical trials and reviews) published between January 2015 and June 2019, in English and Spanish. Results: The literature review exposed the complex relationship that xists between the immune system and tumors. It also revealed that the factors capable of influencing a subject’s response to immune checkpoint inhibitors are multiple, heterogeneous and ill understood, which makes it difficult to obtain simple and/or universal predictive biomarkers. Conclusions: The only biomarkers currently used in clinical practice include the expression of the programmed cell death ligand-1 and microsatellite instability/ deficient DNA mismatch repair, but their usefulness is limited. Tumor mutational burden and gene signatures associated to IFN-γ could become useful biomarkers once determination techniques and cutoff points are systematized.